Research approaches to networked employment services: A systematic review. (1st April 2020) - Andreassen, Tone A.; Breit, Eric; Saltkjel, Therese
Abstract: Research on networked services aimed at the (re)employment of groups marginalised from the labour market has gained momentum in different scholarly traditions (e.g., public administration, healthcare and social policy), but the topic remains somewhat fragmented. In this paper, we systematise and synthesise this research with the aim of outlining distinct research approaches, facilitating increased cross‐disciplinary understandings and promoting interdisciplinary research. Based on a systematic review of the literature (1990–2018, n = 273), we highlight four dominant research approaches: rehabilitation, disability, welfare and governance. We show that these research approaches involve distinct conceptualisations of labour market inclusion, networked services and the target groups. Nevertheless, the research approaches also apply similar terms and concepts (e.g., partnership, collaboration) but with different (more or less implicit) connotations, which lead to fragmentation. We do not suggest that there be a unified use of concepts across traditions; however, we argue for the necessity of increased awareness of the similarities and differences between these research traditions in order to increase understanding of the networked employment services available to marginalised groups.